Electron spectroscopic study of nanoplasma formation triggered by intense soft x-ray pulses - Niozu, Akinobu; Gokhberg, Kirill; Kuleff, Alexander I.; Cederbaum, Lorenz S. (The journal of chemical physics, 2019)
Using electron spectroscopy, we investigated the nanoplasma formation process generated in xenon clusters by intense soft x-ray free electron laser (FEL) pulses. We found clear FEL intensity dependence of electron spectra. Multistep ionization and subsequent ionization frustration features are evident for the low FEL-intensity region, and the thermal electron emission emerges at the high FEL intensity. The present FEL intensity dependence of the electron spectra is well addressed by the frustration parameter introduced by Arbeiter and Fennel [New J. Phys. 13, 053022 (2011)].